2006
DOI: 10.1128/jcm.00175-06
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Transcription-PCR-Enzyme-Linked Immunosorbent Assay for Rapid Detection and Differentiation of Alphavirus Infections

Abstract: Due to the lack of a rapid, simple, and inexpensive assay for detecting alphavirus infections, we combined a reverse transcription-PCR with an enzyme-linked immunosorbent assay (RT-PCR-ELISA) to identify human pathogenic alphaviruses that are endemic in the New World. By combining the sensitivity of PCR, the detection simplicity of ELISA, and the specificities of DNA probes, this method rapidly detected and differentiated closely related species and subtypes of several medically important alphaviruses. After a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
1
18
0
9
Order By: Relevance
“…Examination of these mutants revealed that L526 and L528 were required for function of the NES, while V521 was not necessary. Sequence analysis of the identified NES across 10 representative alphaviruses revealed that the presence of a hydrophobic residue at VEE position 526 is conserved and that the leucine residue at VEE position 528 is highly conserved (7,13,27,30,37,54,57,62,64).…”
Section: Comparison Of the Nlss Of Sfv And Veementioning
confidence: 99%
“…Examination of these mutants revealed that L526 and L528 were required for function of the NES, while V521 was not necessary. Sequence analysis of the identified NES across 10 representative alphaviruses revealed that the presence of a hydrophobic residue at VEE position 526 is conserved and that the leucine residue at VEE position 528 is highly conserved (7,13,27,30,37,54,57,62,64).…”
Section: Comparison Of the Nlss Of Sfv And Veementioning
confidence: 99%
“…La mayoría de los aislamientos del virus Mayaro en mosquitos se obtuvo a partir de Haemagogus recolectados en Brasil durante períodos interepidémicos, lo cual sugiere que podrían estar desempeñando un importante papel en el mantenimiento del virus en su ciclo enzoótico (33) (figura 3). Por otra parte, en muchas localidades donde abundan estas especies se ha encontrado alta seroprevalencia de anticuerpos contra virus Mayaro en monos de vida silvestre, que son la fuente alimentaria predilecta de los mosquitos Haemagogus; en los humanos, existe mayor seroprevalencia contra el virus Mayaro en la población de trabajadores agrícolas y exploradores (10)(11)(12)(13)33,39), patrón similar al que se presenta con el virus de la fiebre amarilla.…”
Section: Ciclo De Transmisión Del Virus Mayaro Artrópodos Vectoresunclassified
“…Un diagnóstico clínico del mal de Mayaro con base en la sintomatología inicial, es confuso por la existencia de cuadros clínicos similares, incluso con otros grupos antigénicos como el dengue y Oropuche, por lo que es de gran importancia emplear métodos diagnósticos inmunológicos y moleculares eficientes (11,13). Los métodos de laboratorio utilizados son el aislamiento viral mediante la inoculación de cultivos celulares en ratones experimentales con posterior aplicación (13,33,77,78).…”
Section: Brotes En Humanos Sintomatología Y Diagnósticounclassified
See 2 more Smart Citations